أثر الاستثمار الأجنبي المباشر على النمو الاقتصادي في الجزائر خلال الفترة - )9109 0991( باستخدام نموذج الانحدار الذاتي للفجوات الزمنية الموزعة ( ARDL ): The effect of foreign direct investment on economic growth in Algeria over the period of (1990-2019) using the Autoregressive Distributed lag (ARDL) - الناصر مبرك,; عيسى دراجي, (Journal of North African Economies, 2025)
The paper aims to measure the effect of foreign direct investment inflows on economic growth in algeria during the period 1990-2019, using the Autoregressive Distributed lag (ARDL), The study concluded that there is a long-term equilibrium relationship between economic growth and foreign direct investment and other variables, And that every increase in foreign direct investment flows of 1% leads to an increase in the growth rate of 0.011%, and the results also showed the existence of a dynamic short-run relationship between the variables. As 65% of short-run errors are corrected in one time in order, to return to equilibrium in the long-run